La prueba en delitos de violación y el debido proceso - Zambrano Moreira, María Milena (2021)
Background: The evidence in the criminal process is a fundamental aspect, and it is more so in the crimes of sexual rape, because the certainty of its existence is what will allow the judge to issue a sentence in favor or against the accused. Then study the way in which this type of evidence is valued, and the elements that support it in determining the parameters that the criminal judge must consider when passing sentence in the crimes of rape. Objective: To analyze the evidence in rape crimes and due process in Ecuador. Methodology: The design of this research is mixed qualitative-quantitative, documentary, for which the legal-doctrinal methods were used, observation of judgments of the Constitutional Court of Ecuador and analysis of interviews, in order to build an interpretation….